Modelling the potential benefits increased active travel - Caulfield, Brian; Carroll, Paraic; Ahern, Aoife (My University, 2019)
This research examines the behavioural response of commuters within the Greater Dublin Area (GDA), Ireland, to a range of policy incentives designed to encourage travellers to make greater use of sustainable travel modes for work. Several policy measures were evaluated using discrete choice and four stage modelling methods, to estimate the propensity of commuters to shift to active modes use (walking and cycling) rather than single occupancy vehicle (SOV). As a means of appraising the hypothetical introduction of a range of active mode policy incentives, a stated preference experiment (SP) was created as an instrument for gathering decision making, mode choice and socio-demographic data from a sample of commuters in the GDA, based on a number of designed policy scenarios. Extensive transport modelling work was subsequently conducted with the National Transport Authority (NTA) of Ireland using the National Regional Modelling System (RMS). A representation of the policy changes explored in the SP experiment was made in this four-stage transport model in order to produce real-life estimates of trip making behaviour and mode share, to test the behavioural response of the introduction of the policy incentives. Changes to parameters in the Mode Choice and Trip Assignment stages of the four-stage model were made to account for improvements made to the infrastructure and time attributes of walking and cycling in the model. The modifications were made based on ‘Do Nothing/Base’, ‘Do Something’, and ‘Do Maximum’ scenarios, which were determined by attribute level values taken from the SP survey. The findings produced in this study show a marked inelasticity of commuters to react in response to improvements made to the level of service of cycling, while on the contrary exhibiting high levels of elasticity to changes made to pedestrian infrastructure. Outputs from these model scenarios found that pedestrians in the GDA were most sensitive to the policy incentives tested. The results highlight that investing in improvements to the public realm may be a more worthwhile investment in order to encourage a modal shift to walking for commuting trip purposes.
PUBLISHED
Keywords: Commuting; Active travel; Transport infrastructure; Smart & Sustainable Planet; Environmental Impacts of Transport; Transport